Modelling Dynamic Topologies via Extensions of VDM-RT - Nielsen, Claus Ballegaard (Technical Report Electronics and Computer Engineering, 2012)
Only a few formal methods include descriptions of the network topology that the modelled system is deployed onto. In VDM Real-Time (VDM-RT) this has been enabled for distributed systems that have a static structure. However, when modelling dynamic systems this fixed topology becomes an issue. Systems with highly distributed and alternating relationships cannot be expressed correctly in a static model. This document describes how VDM-RT can be extended with new language constructs to enable the description of dynamic reconfiguration of the network topology during the runtime execution of a model. The extension is developed on the basis of a case study involving a dynamic system that has a constant changing system topology. With a basis in the case study a model is developed that uses the static version of VDM-RT in order to reveal the limitations of the language. The case study is then revisited where the capabilities of the proposed reconfiguration extension are applied to the model, and the value of having the extension is evaluated. We expect that other notations can benefit from the experiences reported here.